2015
DOI: 10.1111/ppa.12468
|View full text |Cite
|
Sign up to set email alerts
|

Silicon application enhances resistance to xanthomonas wilt disease in banana

Abstract: Silicon (Si) has been reported to be a beneficial element and shown to enhance disease resistance in many crops, although it is not regarded to be critical for plant growth and development. In this study, the potential effect of Si supplementation on resistance to banana xanthomonas wilt (BXW) disease was evaluated using various banana cultivars. Si application at a concentration of 200 mg per plant per week was found to be optimal in enhancing resistance to BXW without any detrimental effects on plant growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 34 publications
2
8
0
1
Order By: Relevance
“…Thus, the application of Si can differentially affect plant growth and development, depending on the internal mechanisms that the genotype has to metabolize this element (Ouellette et al, 2017). Biological responses of plants to Si can be a consequence of the apoplastic obstruction caused by excesive Si deposition in the cell wall (Coskun et al, 2019), which can trigger hormetic effects (Mburu et al, 2016;Agathokleous & Calabrese, 2020). In plants, Si is deposited as the solid, hydrated oxide SiO 2 ‱nH 2 O, known as silica gel, following polymerization of orthosilicic acid (Si(OH) 4 or H 4 SiO 4 ; the only form of Si available to plants) (Gropper & Smith, 2018).…”
Section: Discussion Si Stimulates Growth Of Pepper Plants In a Hormetmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the application of Si can differentially affect plant growth and development, depending on the internal mechanisms that the genotype has to metabolize this element (Ouellette et al, 2017). Biological responses of plants to Si can be a consequence of the apoplastic obstruction caused by excesive Si deposition in the cell wall (Coskun et al, 2019), which can trigger hormetic effects (Mburu et al, 2016;Agathokleous & Calabrese, 2020). In plants, Si is deposited as the solid, hydrated oxide SiO 2 ‱nH 2 O, known as silica gel, following polymerization of orthosilicic acid (Si(OH) 4 or H 4 SiO 4 ; the only form of Si available to plants) (Gropper & Smith, 2018).…”
Section: Discussion Si Stimulates Growth Of Pepper Plants In a Hormetmentioning
confidence: 99%
“…In banana (Musa spp. L.), the application of 200 mg Si per week resulted in a stimulatory effect leading to the beneficial growth attributes, whereas treatments with 500 and 1,000 mg Si per week triggered inhibitory responses, resulting in detrimental effects evidenced by stunting and discoloration of the leaf edges (Mburu et al, 2016). Negative effects such as stunting, deformed flowers and delay in flowering were also observed in sunflowers at high concentrations of Si, thus suggesting Si application can vary from beneficial to detrimental depending on the source and concentration used (Kamenidou, Cavins & Marek, 2008;Kamenidou, Cavins & Marek, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations are founded on the management principles used to deal with other banana bacterial wilt diseases, such as Moko disease (Thwaites et al, 2000). Recent reports have indicated that silicon concentrations above 200 mg/week induce resistance to BXW and thus may augment existing control measures through integrated Xcm management options (Mburu et al, 2016).…”
Section: Managementmentioning
confidence: 99%
“… Upgrade/maintain leaf cuticle thickening and leaf stomata crystals [ 121 ] Stalk borer ,, Decreased % stalks and length bored [ 122 ] Brown rust ,, Physical and biochemical [ 123 ] Euschistusheros Soybean ( Glycine max ) Upregulated non-preference and antibiosis resistances [ 124 ] Powdery mildew Arabidopsis ( Arabidopsis thaliana) Physio-biochemical activities increased and/or balanced [ 58 , 75 , 125 ] Black sigatoka Fusarium wilt Root rot Xanthomonas wilt Banana ( Musa spp.) ,, [ 126 – 129 ] Powdery mildew Barley ( Hordeum vulgare ) Improve physiological performance [ 130 ] Angular leaf spot Bean ( Phaseolus vulgaris ) ,, [ 131 ] Powdery mildew Black gram ( Vigna mungo ) Enhanced expression of genes [ 132 ] Dollar spot Bentgrass ( Agrostis stolonifera ) Improve physiological and biochemical characteristics [ 90 , 133 ] …”
Section: Introductionmentioning
confidence: 99%